Association by Hydrogen Bonding of Mononucleotides in Aqueous Solution - Raszka, Matthew (1972)
Evidence for hydrogen bonding between 5′-ribonucleotides in water has been obtained from a 220-MHz proton magnetic resonance study of nitrogenous protons. The amino groups of GMP, AMP, and CMP exhibit proton resonance lines which are somewhat broadened by proton exchange with the solvent at 0°; their downfield Shifts in mixtures of mononucleotides provide the basis for the following order of base-pairing tendencies: GMP·CMP > AMP·UMP. Hydrogen bonding is also observed in other pairs of mononucleotides, notably GMP·UMP, AMP·CMP, and CMP·UMP, to a lesser extent in GMP·IMP, CMP·XMP, and possibly in CMP·IMP. In agreement with previous reports, hydrophobic interactions of mononucleotides have also been observed; base pairing occurs in addition to vertical stacking of these bases, their hydrogen bonding to water, or self-association. Only CMP shows clear evidence of self-association via hydrogen bonding in water; the evidence for GMP is less direct, and that for AMP is negative. This lack of observable self-association may occur as a result of competition from strong stacking interactions. Only CMP shows restricted rotation of the amino group at 0° and neutral pH. As expected, higher temperatures increase the rate of rotation of the amino group for CMP, as well as accelerate the rate of proton exchange between water and the amino protons of mononucleotides. High-resolution proton magnetic resonance spectroscopy could prove to be a valuable tool in mapping out the specificities conferred by hydrogen bonding between biomolecules in aqueous solution.